Call for papers - GJAE (German Journal of Agricultural Economics, 2013)
European agricultural development, climate change and food security interact in complex ways. Climate change, for example, will induce regional shifts of crop production, while mitigation measures in the livestock sector will increase production costs, especially in case major reduction schemes are agreed upon like the EU goal of 80% emission reduction by 2050. Such mitigation measures may have strong effects on food supplies and food security, both inside Europe, and also on a global scale. European agriculture also seeks for opportunities implementing climate smart agriculture, to balance mitigation/adaptation strategies, while maintaining productivity in agriculture. European strategies for smart, green, and inclusive growth also aim at increasing the role of the biobased economy, processing agro-raw material for biofuels, pharmaceutics, textile and new bio-medical material. What are potential win-win actions for mitigation that could reduce costs and emissions? How to address water scarcity as part of adaptation strategies in agriculture to cope with climate change? What are the relevant economic drives of agricultural development at different scales (farm, sectoral, regional, European, and global)? How does climate change impact international trade, both within Europe and with other non-European countries? Against this background the special issue aims at understanding the recent developments related to European agriculture and climate change, particularly in Germany and the EU. The focus will be on quantitative modelling and empirical analyses. Topics: • Examples of existing tools • Linking economic and biophysical models • Modelling land use and climate change • Water, agriculture, and climate change. Submission procedure: Please submit your full paper to Floor Brouwer (e-mail: floor.brouwer@wur.nl). For the full paper submission please follow the “Instruction for Authors” of the GJAE. Full papers will follow the usual double-blind review process of the GJAE. Papers that pass the review process and cannot be fitted into the special issue will be published in a regular issue of the GJAE. Deadlines: Submission of full papers for review: 01.10.2013. The special issue will be published as the third issue at 01.09.2014.